A high-toughness cement-based composite material based on reinforcing fibers and a method for producing the same
Patent Information
- Application Number
- CN202611005149.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-07
- Publication Date
- 2026-09-15
Smart Images

Figure CN122749025A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of cement composite materials technology, and in particular relates to a high-toughness cement-based composite material based on reinforcing fibers and its preparation method. Background Technology
[0002] Cement-based composite materials are currently the most widely used building materials, but they have inherent defects such as high brittleness, low tensile strength, and susceptibility to cracking. To overcome these defects, fibers are usually introduced into the cement matrix. The bridging effect of the fibers can prevent crack propagation and improve the toughness and ductility of the material.
[0003] However, a core technical contradiction has long existed in the actual preparation and application of fiber-reinforced cementitious composites (FRCCs): the antagonistic relationship between fiber dispersibility and interfacial adhesion. To achieve high toughness, fibers need to be uniformly dispersed in the matrix to prevent stress concentration and internal defects caused by fiber agglomeration; however, to improve reinforcement and toughening efficiency, a sufficiently strong interfacial bond is required between the fiber and the cement matrix to ensure effective stress transfer from the matrix to the fiber. Traditional solutions typically proceed in steps: first, water-reducing agents or dispersants are used to achieve uniform fiber dispersion, and then interfacial adhesion is achieved by relying on the rough surface of the fibers themselves or chemical coatings. However, commonly used dispersants (such as polycarboxylate superplasticizers), while adsorbing onto the fiber surface and achieving dispersion through electrostatic repulsion or steric hindrance, also form an inert organic adsorbed layer on the fiber surface. While this "lubricating film" aids in dispersion, it severely hinders the direct contact and chemical bonding between fibers and cement hydration products (such as CSH gel and calcium hydroxide), leading to a significant decrease in interfacial bond strength. This causes the fibers to be pulled out prematurely under stress, preventing them from fully realizing their reinforcing and toughening potential. This contradiction—"dispersion at the expense of interfacial bonding, and interfacial bonding at the expense of dispersion"—severely restricts further improvements in the performance of high-toughness cement-based composite materials.
[0004] Furthermore, in the application of high-performance fibers, the interfacial bond strength between the fiber and the cement matrix is not necessarily better the higher it is. If the bond is too strong, the fiber at the crack tip will break under the slight displacement during pull-out, leading to brittle failure of the material; if the bond is too weak, the fiber will be easily pulled out, with limited energy dissipation. Therefore, precisely controlling the interfacial bond strength within an optimal range, allowing the fiber to undergo a complete "debonding-slipping-pull-out" process during pull-out, thereby maximizing energy dissipation through pull-out work, is key to achieving ultra-high toughness. Traditional methods struggle to achieve precise and dynamic control of the interfacial microstructure and bond strength.
[0005] Therefore, how to resolve the inherent contradiction between fiber dispersion and interfacial bonding, and achieve precise control of interfacial bonding strength, thereby synergistically improving the workability, mechanical properties and toughness of cement-based composite materials, is a key technical challenge that urgently needs to be addressed in this field. Summary of the Invention
[0006] To address the aforementioned issues, this application provides a high-toughness cement-based composite material based on reinforced fibers and its preparation method.
[0007] This application first provides a high-toughness cement-based composite material based on reinforcing fibers, comprising cement, reinforcing fibers, bio-based cementitious material, gluconate, admixtures, mineral powder and water; the bio-based cementitious material is composed of acid-degraded carrageenan and enzymatically hydrolyzed sericin polypeptide.
[0008] Furthermore, it comprises the following components by weight: 100-300 parts cement, 1-8 parts reinforcing fiber, 0.5-5 parts bio-based cementitious material, 0.5-4 parts gluconate, 30-100 parts admixture, 20-80 parts mineral powder, and 50-150 parts water.
[0009] Furthermore, the mass ratio of acid-degraded carrageenan to enzymatically hydrolyzed sericin polypeptide is 1:(0.2-1).
[0010] Furthermore, the preparation method of the acid-degraded carrageenan includes the following steps:
[0011] 1) Dissolve κ-carrageenan in water and degrade it under acidic conditions to obtain a degradation solution;
[0012] 2) Add soluble calcium salt to the degradation solution, let it stand and then dry it to obtain the acid-degraded carrageenan.
[0013] Furthermore, in step 1), the pH of the acidic conditions is 3.5-4.5; the temperature of the heating degradation is 100-120℃, and the time is 1-3h.
[0014] Furthermore, in step 2), after adding the soluble calcium salt, the calcium ion concentration in the system is 5-7.5 mmol / L.
[0015] Furthermore, the preparation method of the enzymatically hydrolyzed sericin polypeptide includes the following steps: dissolving sericin protein in water and heating it to completely dissolve it to obtain a sericin solution; cooling the sericin solution, adjusting the pH, and then adding alkaline protease to carry out a hydrolysis reaction; after hydrolysis, inactivating the enzyme, purifying, and drying to obtain the enzymatically hydrolyzed sericin polypeptide.
[0016] Furthermore, the hydrolysis reaction is carried out at a temperature of 50-60℃, a pH of 7.5-8.5, and a time of 3-6 hours.
[0017] Furthermore, the reinforcing fiber is polyvinyl alcohol fiber. Preferably, the reinforcing fiber has a length of 6-24 mm and a diameter of 15-60 μm;
[0018] And / or, the gluconate is sodium gluconate or potassium gluconate;
[0019] And / or, the admixture is at least one of fly ash, silica fume, and metakaolin;
[0020] And / or, the ore powder is granulated blast furnace slag powder of grade S95 or above.
[0021] This application also provides a method for preparing a high-toughness cement-based composite material based on reinforced fibers, comprising the following steps:
[0022] S1: Dissolve the bio-based gelling material and gluconate in the first part of the water, which accounts for 30%-60% of the total water volume, and mix them evenly to obtain an active dispersion;
[0023] S2: Add reinforcing fibers to the active dispersion and stir to obtain a pretreated fiber slurry; mix cement, admixtures, and mineral powder evenly to obtain a dry mixture;
[0024] S3: Mix the pretreated fiber slurry, the remaining water and the dry mix and stir evenly to obtain the high-toughness cement-based composite material.
[0025] Compared with the prior art, this application has the following beneficial effects:
[0026] This application constructs a dynamic hydrogen-bonded composite network based on acid-degraded carrageenan / enzymatically hydrolyzed sericin peptides / metal ions to form a film layer on the surface of fibers and inorganic particles that has both dispersive and interfacial activation functions, thereby balancing and improving fiber dispersibility and interfacial adhesion. During the accelerated curing period of cement, OH groups generated during cement hydration... - As the concentration increases, the sulfate ester groups on the carrageenan molecular chain partially dissociate, and the coordinated Ca... 2+ Gradual release provides growth sites for the nucleation of CSH gels, promoting uniform growth of hydration products; during the hardening phase, incompletely released Ca... 2+ It continuously participates in the secondary hydration reaction, generating more CSH gel and ettringite, filling the internal pores of the matrix and improving the later strength.
[0027] Furthermore, gluconate can react with Ca in cement hydration products. 2+The formation of stable chelates slows down the early hydration rate of cement and improves the fluidity of the slurry. Simultaneously, gluconate can synergistically interact with bio-based cementitious materials, further enhancing the stability of the dynamic composite network and improving fiber dispersion. Furthermore, in the later stages of hydration, chelation can regulate the crystal growth of hydration products, optimize the microstructure of the interfacial transition zone, and improve the density, toughness, and strength of the matrix. Attached Figure Description
[0028] Figure 1 This is a schematic diagram of the ultimate tensile strain test data of the cement-based composite material in Example 1 of this application.
[0029] Figure 2 This is a schematic diagram of the ultimate tensile strain test data of the cement-based composite material in the control group of this application.
[0030] Figure 3 This is a schematic diagram of the flexural strength test data of the cement-based composite material in Example 1 of this application.
[0031] Figure 4 This is a schematic diagram of the flexural strength test data of the cement-based composite material in the control group of this application. Detailed Implementation
[0032] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0034] When using “including,” “having,” and “contains” as described herein, the intention is to cover non-exclusive inclusion, unless an explicit qualifying term such as “only,” “consisting of,” etc., is used, in which case another component may be added.
[0035] The terms "preferred," "more preferably," "better," and "even better" used in this application refer to embodiments of this application that provide certain beneficial effects under certain circumstances. However, other embodiments may also be preferred under the same or other circumstances. Furthermore, the description of one or more preferred embodiments does not imply that other embodiments are unavailable, nor is it intended to exclude other embodiments from the scope of this application. That is, in this application, "preferred," "more preferably," "better," and "even better" are merely descriptions of implementations or embodiments with better effects, but do not constitute a limitation on the scope of protection of this application.
[0036] In this application, terms such as "further," "even more," and "particularly" are used for descriptive purposes and indicate differences in content, but should not be construed as limiting the scope of protection of this application.
[0037] In this application, "at least one" means one or more, such as one, two, or more. "Multiple" or "several" means at least two, such as two, three, etc., and "multi-layered" means at least two layers, such as two layers, three layers, etc., unless otherwise explicitly specified. In the description of this application, "several" means at least one, such as one, two, etc., unless otherwise explicitly specified.
[0038] When a numerical range is disclosed herein, the range is considered continuous and includes the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.
[0039] Unless otherwise specified, all steps in this application may be performed sequentially or randomly. For example, the method comprising steps (a) and (b) indicates that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order; for example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc. Unless otherwise stated, singular terms may include plural forms and should not be construed as having a quantity of one.
[0040] In this application, "above" or "below" includes the number itself. For example, "below 1" includes 1.
[0041] In this application, room temperature refers to 0~40℃, including but not limited to 10~40℃, or further to 20~30℃.
[0042] The present application will be further illustrated by the following examples, but these examples do not limit the scope of the present application.
[0043] When numerical ranges are given in the embodiments, it should be understood that, unless otherwise stated in this application, both endpoints of each numerical range and any value between the two endpoints may be selected. Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. All reagents or instruments whose manufacturers are not specified are conventional products that can be purchased commercially. In addition to the specific methods, equipment, and materials used in the embodiments, based on the knowledge of the prior art possessed by one of ordinary skill in the art and the description in this application, any prior art methods, equipment, and materials similar to or equivalent to those described, used, or made by the methods, equipment, and materials in the embodiments of this application may be used to implement this application.
[0044] Example 1
[0045] The high-toughness cement-based composite material based on reinforced fiber in this embodiment includes the following raw materials by weight: 200kg cement, 3kg reinforcing fiber, 1kg bio-based cementitious material, 1.5kg sodium gluconate, 65kg admixture, 50kg mineral powder, and 105kg water.
[0046] The cement used is P·II52.5 silicate cement. The reinforcing fiber is high-strength, high-modulus PVA fiber. The admixture is fly ash. The mineral powder is blast furnace slag.
[0047] The bio-based gelling material is composed of acid-degraded carrageenan and enzymatically hydrolyzed sericin peptides in a mass ratio of 1:0.5. The acid-degraded carrageenan is prepared using a method comprising the following steps:
[0048] 1) Weigh 25g of κ-carrageenan and dissolve it in distilled water at 80℃, controlling the concentration of κ-carrageenan in the system to be 10g / L. Then add acetic acid to adjust the pH to 4.0, heat to 110℃ and degrade for 1.5h to obtain the degradation solution.
[0049] 2) Add calcium lactate to the degradation solution, control the calcium ion concentration in the system to 6.5 mmol / L, let stand overnight, and freeze dry to obtain the final product.
[0050] The enzymatically hydrolyzed sericin peptides were prepared using the following steps: 100g of sericin was weighed and added to 2000mL of distilled water. The mixture was stirred until homogeneous to form a 5wt% sericin suspension. The pH was adjusted to 8.5 with 1M NaOH solution. The suspension was heated to 90℃ and stirred for 30 minutes to completely dissolve the sericin. The solution was filtered through double-layered gauze to remove insoluble impurities, resulting in a clear sericin solution. The sericin solution was cooled to 55℃ and the pH was adjusted to 8.0. 2.5g of alkaline protease was added and stirred until homogeneous. The solution was then hydrolyzed at 55℃ and pH 8.0 for 4 hours with constant stirring. During the reaction, the pH was maintained at 8.0±0.1. After hydrolysis, the reaction solution was heated to completely inactivate the alkaline protease. The solution was cooled to room temperature and the pH was adjusted to 7.0. The solution was then vacuum filtered and freeze-dried to obtain the final product.
[0051] The preparation method of the high-toughness cement-based composite material based on reinforced fibers in this embodiment includes the following steps:
[0052] S1: Dissolve the bio-based gelling material and sodium gluconate in the first part of water, which accounts for 55% of the total water volume, and mix them evenly to obtain an active dispersion.
[0053] S2: Add reinforcing fibers to the active dispersion and stir to obtain a pretreated fiber slurry; mix cement, admixtures, and mineral powder evenly to obtain a dry mixture;
[0054] S3: Mix the pretreated fiber slurry, the remaining water and the dry mix and stir evenly to obtain the high-toughness cement-based composite material.
[0055] Example 2
[0056] The high-toughness cement-based composite material based on reinforced fiber in this embodiment includes the following raw materials by weight: 200kg cement, 3kg reinforcing fiber, 1kg bio-based cementitious material, 1.5kg potassium gluconate, 65kg admixture, 50kg mineral powder, and 105kg water.
[0057] The cement used is P·II52.5 silicate cement. The reinforcing fiber is high-strength, high-modulus PVA fiber. The admixture is fly ash. The mineral powder is blast furnace slag.
[0058] The bio-based gelling material is composed of acid-degraded carrageenan and enzymatically hydrolyzed sericin peptides in a mass ratio of 1:0.75.
[0059] Acid-degraded carrageenan is prepared by a method comprising the following steps:
[0060] 1) Weigh 25g of κ-carrageenan and dissolve it in distilled water at 80℃, controlling the concentration of κ-carrageenan in the system to be 10g / L. Then add acetic acid to adjust the pH to 4.0, heat to 110℃ and degrade for 1.5h to obtain the degradation solution.
[0061] 2) Add calcium lactate to the degradation solution, control the calcium ion concentration in the system to 6.5 mmol / L, let stand overnight, and freeze dry to obtain the final product.
[0062] The enzymatically hydrolyzed sericin peptides were prepared using the following steps: 100g of sericin was weighed and added to 2000mL of distilled water. The mixture was stirred until homogeneous to form a 5wt% sericin suspension. The pH was adjusted to 8.5 with 1M NaOH solution. The suspension was heated to 90℃ and stirred for 30 minutes to completely dissolve the sericin. The solution was filtered through double-layered gauze to remove insoluble impurities, resulting in a clear sericin solution. The sericin solution was cooled to 55℃ and the pH was adjusted to 8.0. 2.5g of alkaline protease was added and stirred until homogeneous. The solution was then hydrolyzed at 55℃ and pH 8.0 for 4 hours with constant stirring. During the reaction, the pH was maintained at 8.0±0.1. After hydrolysis, the reaction solution was heated to completely inactivate the alkaline protease. The solution was cooled to room temperature and the pH was adjusted to 7.0. The solution was then vacuum filtered and freeze-dried to obtain the final product.
[0063] The preparation method of the high-toughness cement-based composite material based on reinforced fibers in this embodiment includes the following steps:
[0064] S1: Dissolve the bio-based gelling material and potassium gluconate in the first part of the water, which accounts for 55% of the total water volume, and mix them evenly to obtain an active dispersion.
[0065] S2: Add reinforcing fibers to the active dispersion and stir to obtain a pretreated fiber slurry; mix cement, admixtures, and mineral powder evenly to obtain a dry mixture;
[0066] S3: Mix the pretreated fiber slurry, the remaining water and the dry mix and stir evenly to obtain the high-toughness cement-based composite material.
[0067] control group
[0068] The cement-based composite material in this control group includes the following raw materials by weight: 200 kg cement, 3 kg reinforcing fiber, 1 kg carrageenan, 1.5 kg sodium gluconate, 65 kg admixture, 50 kg mineral powder, and 105 kg water.
[0069] The cement used is P·II52.5 silicate cement. The reinforcing fiber is high-strength, high-modulus PVA fiber. The admixture is fly ash. The mineral powder is blast furnace slag.
[0070] The preparation method of the high-toughness cement-based composite material based on reinforced fibers in this control group includes the following steps:
[0071] S1: Dissolve the carrageenan and sodium gluconate in the first part of water, which accounts for 55% of the total water volume, and mix them evenly to obtain an active dispersion.
[0072] S2: Add reinforcing fibers to the active dispersion and stir to obtain a pretreated fiber slurry; mix cement, admixtures, and mineral powder evenly to obtain a dry mixture;
[0073] S3: Mix the pretreated fiber slurry, the remaining water and the dry mix and stir evenly to obtain the high-toughness cement-based composite material.
[0074] Performance testing
[0075] The cement-based composite materials from Example 1 and the control group were subjected to ultimate tensile strain and flexural strength tests according to standards JC / T 2461-2018 and GB / T50081-2019. Specific test results are as follows: Figures 1-4 As shown. Analysis Figures 1-4 It can be seen that the cement-based composite material of this application has superior ultimate tensile strain and higher flexural strength, and excellent mechanical properties.
[0076] Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A high ductility cementitious composite based on reinforcing fibers, characterized in that, It comprises cement, reinforcing fibers, bio-based cementitious materials, gluconate, admixtures, mineral powder, and water; the bio-based cementitious materials are composed of acid-degraded carrageenan and enzymatically hydrolyzed sericin polypeptides.
2. The high toughness fiber reinforced cementitious composite material according to claim 1, wherein: It contains the following components by weight: 100-300 parts cement, 1-8 parts reinforcing fiber, 0.5-5 parts bio-based cementitious material, 0.5-4 parts gluconate, 30-100 parts admixture, 20-80 parts mineral powder, and 50-150 parts water.
3. The high toughness fiber reinforced cementitious composite material according to claim 1 or 2, wherein: The mass ratio of acid-degraded carrageenan to enzymatically hydrolyzed sericin polypeptide is 1:(0.2-1).
4. The high toughness fiber reinforced cementitious composite material of claim 1, wherein: The method for preparing acid-degraded carrageenan includes the following steps: 1) Dissolve κ-carrageenan in water and degrade it under acidic conditions to obtain a degradation solution; 2) Add soluble calcium salt to the degradation solution, let it stand and then dry it to obtain the acid-degraded carrageenan.
5. The high toughness fiber reinforced cementitious composite material according to claim 4, wherein: In step 1), the pH of the acidic conditions is 3.5-4.5; the temperature for the heating degradation is 100-120℃, and the time is 1-3h.
6. The high toughness fiber reinforced cementitious composite material of claim 4, wherein: In step 2), after adding the soluble calcium salt, the calcium ion concentration in the system is 5-7.5 mmol / L.
7. The high toughness fiber reinforced cementitious composite material of claim 1, wherein: The preparation method of the enzymatically hydrolyzed sericin polypeptide includes the following steps: dissolving sericin protein in water and heating it to completely dissolve it to obtain a sericin solution; cooling the sericin solution, adjusting the pH, and then adding alkaline protease to carry out a hydrolysis reaction; after hydrolysis, inactivating the enzyme, purifying, and drying to obtain the enzymatically hydrolyzed sericin polypeptide.
8. The high toughness fiber reinforced cementitious composite material according to claim 7, wherein: The hydrolysis reaction is carried out at a temperature of 50-60℃, a pH of 7.5-8.5, and a time of 3-6 hours.
9. The high toughness fiber reinforced cementitious composite material of claim 1, wherein: The reinforcing fiber is polyvinyl alcohol fiber; And / or, the gluconate is sodium gluconate or potassium gluconate; And / or, the admixture is at least one of fly ash, silica fume, and metakaolin; And / or, the ore powder is granulated blast furnace slag powder of grade S95 or above.
10. A method of manufacturing a high toughness fiber reinforced cementitious composite material according to claim 1, characterized in that: Includes the following steps: S1: Dissolve the bio-based gelling material and gluconate in the first part of the water, which accounts for 30%-60% of the total water volume, and mix them evenly to obtain an active dispersion; S2: Add reinforcing fibers to the active dispersion and stir to obtain a pretreated fiber slurry; mix cement, admixtures, and mineral powder evenly to obtain a dry mixture; S3: Mix the pretreated fiber slurry, the remaining water and the dry mix and stir evenly to obtain the high-toughness cement-based composite material.